Constraints from Spectrum of Scalar Fields in the 3-3-1 Model with CKM Mechanism - Hoang, Ngoc Long; Nguyen, Van Hop; Nguyen, T. Nhuan; Hoang, Hanh Phuong (Communications in Physics, 2019)
The vacuum stability conditions are implemented for the 3-3-1 model of observed fermion masses and mixings. We show that for the Higgs squared mass matrices, the condi- tions for semi-definition of the diagonal elements are most important since other constraints are followed from the first ones.